Prediction of Coronavirus anxiety based on the mental strength of girls: With the mediating role of self-criticism - Mahmoodi, Fatemeh; Abdian, Zahra; Maali Mehrabani, Elham; Sarikhani, Marzieh (Applied Family Therapy Journal (AFTJ), 2021)
Aim: This study aimed to predict Coronavirus anxiety based on the mental strength with the mediating role of self-criticism among girl university students. Methods: The present study was descriptive and correlational, and the statistical population included all female students of Tonekabon Azad University. And according to Cochran’s formula, 200 people among this population were selected by the convenience sampling method. The research instruments included Alipour et al.’s Corona Anxiety Scale (2015), Kola, Erle, and Seville’s (2002) Psychological Strength Questionnaire, and the Thompson and Zorof (2004) scale for self-critical levels. The data were analyzed using a correlation coefficient test and simultaneous hierarchical regression by SPSS23 software. Results: The results indicated that mental strength was a significant predictor of Coronavirus anxiety (P = 0.01), and self-criticism was a significant predictor of Coronavirus anxiety. Also, when self-criticism is presented as a mediating variable in the relationship between psychological strength and Coronavirus anxiety, this relationship decreases (P = 0.01). Conclusion: According to the results, paying attention to mental strength by using self-criticism plays a significant role in the level of experiencing Coronavirus anxiety among female students.